Oscar's Lonely Christmas - Webb, Holly; Illustrated by Williams, Sophy (New York Scholastic Australia Pty Ltd., 2010)
Hannah has always wanted a dog and can't believe her luck when her parents finally say yes. Better still, they're getting a Dalmatian - Hannah's dream dog. Oscar loves Hannah and soon settles into his new home. But as it gets closer to Christmas, Hannah needs to rehearse for her school play, and has less and less time for long walks and games with her puppy. Oscar feels lonely and neglected. Why doesn't Hannah want to be with him anymore?
Include Illustrations
Keywords: Puppies -- Dalmatian dog -- Human-animal relationships